Epistemologia pluralizada e história da psicologia (Scientiae Studia, 2009)
Wilhelm Wundt and William James opus are used here to argue that psychology emerges as scientific project in the end of nineteenth-century. Psychology as science and as metaphysics is distinguished by this project. From this point of view, history of psychology is to be conceived as history of scientific psychology and prehistory of psychology is to be conceived as history of metaphysical psychology. But Wundt and James conceptions of sciences are different. From the unitary epistemological view, psychology is not constituted as science. In this case, history of psychology is to be conceived as prehistory of this discipline: his history as science will begin only if it achieves unity. From the pluralized epistemological view, history of psychology is to be conceived as history of culture: it is history of psychological and philosophical traditions of thought, and also, history of ideas. It is conclude that, from the pluralized epistemological view, epistemology and history of psychology are turned into anthropological perspective, that is, prehistory of psychology does not exist, and history of psychology may begin in whatever time and place. And, finally, that to elucidate psychology as science depends on history of psychological science and culture.